Coastal engineering (Elsevier Scientific Pub. Co, 1977)
"This international journal is indispensable reading for engineers working in the field of marine and coastal technology. Combining practical application with modern technological and scientific achievements, it publishes fundamental studies as well as case histories on the following aspects of coastal, harbour and offshore engineering: studies on waves and currents; coastal morphology; estuary hydraulics; harbour and offshore structures. Mathematical and physical models as well as constructional aspects and environmental problems relating to these items are also included."
Keywords: Shore protection : Periodicals; Hydraulic engineering : Periodicals; Ocean engineering : Periodicals; Coastal zone management : Periodicals